The Effect of Conventional Laboratory Practical Manuals on Pre-Service Teachers’ Integrated Science Process Skills - ADLIM, Muhammad; NUZULIA, Rusydi; NURMALIAH, Cut (Journal of Turkish Science Education, 2018)
This study explored the effect of conventional laboratory practical manuals on pre-service teachers’ integrated science process skills (ISPS). A validated multiple-choice questionnaire with the ISPS components was used to collect data. No significant difference between pre-service subject-specific teachers’ (biology, physics and chemistry) ISPS scores was found. The ISPS scores significantly increased along with proliferation in lab practical works, except for physics. Pre-service math teachers, who had no lab practical works, showed significantly higher ISPS scores than pre-service science teachers. The results indicated that all pre-service teachers’ ISPS scores fell into intermediate level. Further, it was found that they possessed the lowest scores for such ISPS as identifying and controlling variable, stating operational definition and designing experiments. The common format of the conventional laboratory manual adopted from many universities need to be reformatted for engage learners in all ISPS. To improve learners’ ISPS, higher-order thinking assignments should be intensively given to them.